L’esthétique énactive sense-making au fondement d’une éco-soma-artistique - Alice Dupas (Appareil)
If the issue of eco-gesture extends beyond the field of art and is independent of artistic issues, it is not sure that art, in particular contemporary participatory arts, are perfectly external to this ordinary individual and social life issue. To theorize what would be an art of eco-gesture, one needs to seek an aesthetic theory that takes it efficiently into account and, like the topic it addresses, that has practical, even praxis-oriented dimension. The somaesthetics founded by Richard Shusterman in the 1990s is a pioneering form of praxis-based aesthetics, involving the effective manipulation of the body in order to perfect it in everyday life and, through it, to perfect the aesthetic and artistic experiences of which it is the constitutive thinking foundation. Somaesthetics thus appears as a necessary component of the aesthetic theory we are looking for. However, it is not its achieved version. Indeed, it is in a close aesthetic theory—borrowing also itself from pragmatism—, but one that better defines the body and its environment as well as aesthetics itself, that one can find a useful theory, not only for defining the artistic process but also for founding an “eco-soma-artistic” heuristically responsible for drawing attention, within the artistic sphere, to the aesthetic and praxis-oriented dimensions of eco-gesture. This philosophical aesthetics is called “enactive sense-making aesthetics”.